2021
DOI: 10.1126/sciadv.aaz5236
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity and environmental predictors of permafrost region soil organic carbon stocks

Abstract: Large stocks of soil organic carbon (SOC) have accumulated in the Northern Hemisphere permafrost region, but their current amounts and future fate remain uncertain. By analyzing dataset combining >2700 soil profiles with environmental variables in a geospatial framework, we generated spatially explicit estimates of permafrost-region SOC stocks, quantified spatial heterogeneity, and identified key environmental predictors. We estimated that Pg C are stored in the top 3 m of permafrost region soils. The great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 40 publications
6
167
0
Order By: Relevance
“…Prevailing deposit types are Yedoma (Strauss et al, 2017) and thermokarst deposits (Veremeeva et al, 2021) with the latter covering approximately 58 % of the land area in regions with high Yedoma coverage, and up to 96.4 % in regions with low Yedoma deposit occurrence. These deposits are intermitted by marshes, river valleys and deltas (Veremeeva et al, 2021).…”
Section: Calamagrostis Langsdorfiimentioning
confidence: 99%
See 1 more Smart Citation
“…Prevailing deposit types are Yedoma (Strauss et al, 2017) and thermokarst deposits (Veremeeva et al, 2021) with the latter covering approximately 58 % of the land area in regions with high Yedoma coverage, and up to 96.4 % in regions with low Yedoma deposit occurrence. These deposits are intermitted by marshes, river valleys and deltas (Veremeeva et al, 2021).…”
Section: Calamagrostis Langsdorfiimentioning
confidence: 99%
“…In the context of global climate warming, carbon emissions from Arctic permafrost regions have been identified as a key source of greenhouse gases (GHG), further accelerating the permafrost carbon-climate feedback and increasing atmosphere warming (Schuur et al, 2015;Turetsky et al, 2019;Bowen et al, 2020). An estimated 1300 Petagrams (Pg) of carbon are stored within the upper 3 m of ground in the permafrost region, of which approximately 1000 Pg are perennially frozen (Hugelius et al, 2014;Mishra et al, 2021). The carbon storage and release mechanisms of permafrost had an important role for atmospheric GHG levels during the Late Quaternary (Zimov et al, 2006;Walter et al, 2007;Lindgren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing the underground community should be a priority Our results showed that plant functional community composition and diversity were good predictors of above-ground carbon stocks and ecosystem fluxes whereas a large part of variation in soil organic carbon stocks remained unexplained. This is an issue as most of the carbon in tundra ecosystems is located in the soil (Hugelius et al 2014;Mishra et al 2021).…”
Section: Functional Diversity Of Leaf Economics Increases Ecosystem Functioningmentioning
confidence: 99%
“…Because of the vastness, inaccessibility and extreme climate of the Arctic zone, research in this region is a complex endeavour . There are vast stocks of carbon in permafrost soils (Yu, 2012;Hugelius et al, 2014;Schuur et al, 2013;Strauss et al, 2017;Nichols and Peteet, 2019;Mishra et al, 2021) that have accumulated over the past millennia, which are at increased risk of thawing linked to climate change and its associated Arctic amplification (Schuur et al, 2008;Serreze and Barry, 2011;IPCC, 2014;Schuur et al, 2015;Meredith et al, 2019;Hugelius et al, 2020). With limited insights into current Arctic carbon cycle processes, it is difficult to determine trends and changes in Arctic carbon budgets (Belshe et al, 2013;McGuire et al, 2012;Oechel et al, 2014;Pörtner et al, 2019;Bruhwiler et al, 2021).…”
Section: Section 1: Introductionmentioning
confidence: 99%